New approaches to inequality research with youth: theorizing race beyond the traditions of our disciplines - Tuck, Eve (Routledge, Taylor & Francis Group, 2024)
"For those engaging in research to reduce youth inequality, we know that strong methods are needed alongside strong theorizing about racialization, racism, and racial categorization. This edited volume shares contributors' first person narrations of some of the learning and learning curves, and some of the challenges and disappointments of breaking from the traditions of their fields, and finding new ways to think about race. Drawing on contributors' narrations of how they came to engage with compelling theories of Blackness, Indigeneity, and/or racialization, and how such theories inform the social science research they do with young people, this edited volume tells a multi-disciplinary story about the careful reading and assessment that is required to refuse universal theories of Blackness, Indigeneity, and racialization"--